2012
DOI: 10.1155/2012/452651
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Haemangioma: A Cause for Chronic Pain about the Knee: A Case Report

Abstract: Skeletal muscle haemangiomas are uncommon soft tissue tumors; more than 90% are misdiagnosed initially. They present as chronic pain and swelling in a muscle with or without a history of trauma. Plain X-rays, bone scans, computerized tomography (CT) studies, and angiography studies may not always be specific for this tumor. Diagnostic ultrasound is an appropriate initial imaging modality for suspected haemangioma, although magnetic resonance imaging is the investigation of choice. Many treatment modalities for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Complete excision can be challenging due to the vascularity, and the infiltrative nature of these lesions when intramuscular. Failure to completely excise the lesion is the reason for the high recurrence rate of up to 20 % in the literature [52]. Canavese et al reported no recurrence with wide resection, but higher than 20 % recurrence with marginal resection.…”
Section: Hemangiomamentioning
confidence: 99%
“…Complete excision can be challenging due to the vascularity, and the infiltrative nature of these lesions when intramuscular. Failure to completely excise the lesion is the reason for the high recurrence rate of up to 20 % in the literature [52]. Canavese et al reported no recurrence with wide resection, but higher than 20 % recurrence with marginal resection.…”
Section: Hemangiomamentioning
confidence: 99%
“…These lesions generally appear as areas of high signal intensity on both 𝑇1 and 𝑇2 images compared to most soft tissue tumors, which display intermediate signal intensity on 𝑇1 and high signal intensity on 𝑇2. (14) Ultrasonography (US) shows a venous type signal within isoechogenic or hyperechogenic mass. (4) In our case, the US showed an organized hematoma; however, a soft tissue neoplastic lesion could not be ruled out, particularly as the vascularity was signi cantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…Intramuscular hemangioma presents as a slow-growing mass with compressibility and without pulsations or bruits due to the presence of minor vascular malformations [ 16 , 22 , 23 , 24 ]. Intramuscular hemangioma poses a major diagnostic challenge [ 7 , 11 , 25 ].…”
Section: Discussionmentioning
confidence: 99%